Effects of immunotherapies and clinical outcomes in neurosarcoidosis : a retro- spective cohort study. Issue 6 (27th May 2022) - Arun, Tarunya; Freeman, Sarah; Mistry, Kieran
Abstract : Introduction: Neurosarcoidosis is associated with a high degree of morbidity and mortality and its treat- ments are varied and complex. There is a paucity of information in current literature on patterns of treatment and long term outcomes. This study aimed to evaluate the clinical outcomes and responses to immunosuppressive therapy in a large cohort of biopsy proven neurosarcoidosis patients. Methods: We enrolled 85 patients with a diagnosis of neurosarcoidosis. Prescription patterns and clinical outcomes before and after treatment and differences between the treatment groups were compared using Kruskal Wallis and Mann-Witney U tests. Results: Patients with cranial mononeuropathy were more likely to be treated with steroids alone than patients with brain parenchymal involvement, hydrocephalus and spinal cord presentations who were likely to require second and third line treatments. Commonly used immunosuppressive agents were azathioprine (26%), methotrexate (17.5%) and corticosteroids alone (11%). Just over 85% of patients on corticosteroids went onto second or third line treatments. Patients on steroid monotherapy had the worst outcomes and those on a combination of corticosteroids, azathioprine and infliximab showed superior clinical improvements (p=0.008). Conclusions: Our results provides evidence that early immunosuppressive treatments, with azathioprine, methotrexate and infliximab could effectively improve clinical outcomes in neurosarcoidosis. tarunya1@gmail.com